Petrogenesis and tectonic implications of intrusive rocks in the Jiangjunmu porphyry deposit, East Kunlun orogeny, NW China - Junzhen, Yu; Dexian, Li; Yalin, Gao; Bo, Ma; Youye, Zheng; Khan, Junaid; Tahir, Asma (Frontiers in Earth Science, 2025)
The newly discovered Jiangjunmu Cu–Au deposits are hosted within granodiorite porphyry and K-feldspar granite of the East Kunlun metallogenic belt. Previous understanding of these deposits has been limited due to a lack of comprehensive isotopic data. To address this gap, we present new zircon U–Pb geochronology, whole-rock geochemistry, and Sr–Nd–Pb–Hf isotopic analyses of the Jiangjunmu intrusive rocks. Both intrusive rock samples exhibit nearly identical rare earth element patterns, suggesting they originated from the same source area. The K-feldspar granite (206Pb/238U age: 228 Ma) and the Jiangjunmu granodiorite porphyry intruded into the Jiangjunmu K-feldspar granite porphyry (206Pb/238U age: 234 Ma). They exhibit initial (87Sr/86Sr)ᵢ ratios of 0.70884–0.70944 and 0.70555–0.70913, εNd(t) values of −4.32 to −5.24 and −8.27 to −8.93, 207Pb/204Pb ratios of 15.615–15.677 and 15.664–15.682, and 208Pb/204Pb ratios of 38.443–38.544 and 38.526–38.650, respectively. The Jiangjunmu K-feldspar granite also has high Rb/Sr ratios (0.82), low MgO (0.66–1.19 wt%), Cr (6.6–13.6 ppm), Ni (4.4–6.4 ppm), and Co (55.9–97.2 ppm) contents, indicating an origin from a thickened lower continental crust (TLCC) magma source by partial melting (Sr/Y: 9.4–15.8; La/Yb: 25.6–35.5). Its lower Mg# values (36–39), relatively higher (87Sr/86Sr)ᵢ ratios, lower Sr concentrations (179.8–266.1 ppm), and εHf(t) values (−8.18 to −3.83) suggest that a more evolved upper continental crustal component (heterotypic sandstone) contributed to the formation of the K-feldspar granite during magmatic evolution. The presence of numerous mafic magmatic enclaves (MMEs) in the granodiorite porphyry suggests that the Cu (Au) contents of the Jiangjunmu deposit may have been derived from a mantle source. In association with the tectonic background and regional research, the Jiangjunmu granodiorite porphyry and K-feldspar granite (Th/Sm: 4.2–5.1; Th/Yb:11.5–14.8) formed in a post-collisional orogenic extensional setting after the closure of the Paleo-Tethys Ocean.